Development of an enzyme-linked immunosorbent assay method for typing and quantitation of Klebsiella pneumoniae lipopolysaccharide: application to serotype O1. - Albertí, S (1993)
We describe a method for the typing and quantitation of Klebsiella pneumoniae serotype O1 lipopolysaccharide (LPS) based on inhibition in an enzyme-linked immunosorbent assay of a reaction of known O1 LPS antigen and anti-O1 antibody by unknown LPS extracts. Serotype O1 was found in 32% of the 124 K. pneumoniae clinical isolates tested, showing that this serotype is frequent among the eight O serotypes which have been described previously.